Pencegahan Perkawinan Anak di NTB: Perspektif Kebijakan dan Masyarakat dalam Perspektif Gender - Maghfurrohman, Muhammad; Bima Putri, Nurhastuti; Zulkarnain3; Jidatul Haz, Aaz; Hamim, Khairul (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2024)
This article discusses the phenomenon of preventing child marriage in West Nusa Tenggara (NTB) with a focus on gender policies and perspectives. NTB has the third highest gender bias index in Indonesia, reaching 0.490 after Jambi and Southeast Sulawesi. The phenomenon of child marriage is also widespread in NTB, encouraging policy makers to implement the Marriage Age Maturation Program (PUP) as a prevention effort. This research analyzes PUP as an object of study with a gender perspective from policy makers and society. The factors causing gender bias in preventing child marriage in NTB are described in descriptive-qualitative field research. The research results show that policy makers prioritize gender justice, but the community has an unequal view regarding the implementation of PUP in NTB. The minimal role of women in the public sphere is caused by society's attachment to absolute interpretations of the text, creating three forms of gender bias in NTB women: marginalization, subordination, and stereotypes. The importance of a holistic and inclusive approach in developing policies to prevent child marriage in NTB is highlighted. This article provides insight into increasing policy effectiveness by paying attention to societal norms and attitudes towards gender.